Kepemimpinan Pendidikan Islam Persfektif Humanis - Norhanah, Norhanah; OKTOBERIA, SELVA SUSILA OKTOBERIA (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study discusses leadership in Islamic education from a humanist perspective that places human values as the core of the educational process. Leaders of Islamic educational institutions such as principals are expected not only to carry out administrative functions, but also to be role models who are able to create an inclusive, dialogical and equitable learning environment. The humanistic approach to leadership is based on Islamic teachings that place humans as caliphs on earth and respect the uniqueness and potential of each individual. This study uses a descriptive qualitative method based on literature review and reveals that humanist leadership has a strategic role in fostering a collaborative spirit, building a healthy organizational culture, and responding to the challenges of globalization without ignoring Islamic values. Islamic educational leadership from a humanist perspective is the key to creating educational institutions that are dignified, visionary and able to produce generations with character.